Pneumatosis intestinalis in COVID-19. Issue 1 (9th June 2020) - Meini, Simone; Zini, Chiara; Passaleva, Maria Teresa; Frullini, Anna; Fusco, Francesca; Carpi, Roberto; Piani, Fiorella
Abstract : Introduction: COVID-19 is a respiratory illness due to novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), described in December 2019 in Wuhan (China) and rapidly evolved into a pandemic. Gastrointestinal (GI) tract can also be involved. Case presentation: A 44-year-old man was hospitalised for COVID-19-associated pneumonia. A rapid recovery of respiratory and general symptoms was observed after 1 week of treatment with lopinavir/ritonavir plus hydroxychloroquine and broad-spectrum antibiotics (piperacillin–tazobactam plus teicoplanin). No GI symptoms were reported during hospitalisation, but a lung contrast-enhancement CT (CE-CT) excluding thromboembolism showed, as collateral finding, intraperitoneal free bubbles not present on a previous CT examination; the subsequent abdominal CE-CT described pneumatosis intestinalis (PI) involving the caecum and the right colon. Ciprofloxacin plus metronidazole was started, and the 2-week follow-up CT showed the complete resolution of PI. Discussion: The pathogenesis of PI is poorly understood. PI involving the caecum and right colon has been described for HIV and Cytomegalovirus infections, but, to our best knowledge, never before in COVID-19. We hypothesise a multifactorial aetiopathogenesis for PI, with a possible role of the bowel wall damage and microbiota impairment due to SARS-CoV-2 infection, and we suggest a conservative management in the absence of symptoms.